Penetration of hydrogen peroxide and degradation rate of different bleaching products - Marson, F. C.; Goncalves, R. S. [UNESP]; Silva, C. O.; Cintra, Luciano Tavares Angelo [UNESP]; Pascotto, R. C.; Santos, Paulo Henrique dos [UNESP]; Briso, André Luiz Fraga [UNESP] (Operative Dentistry Inc, 2015)
This study's aim was to evaluate the degradation rate of hydrogen peroxide (H2O2) and to quantify its penetration in tooth structure, considering the residence time of bleaching products on the dental enamel. For this study, bovine teeth were randomly divided according to the bleaching product received: Opalescence Xtra Boost 38%, White Gold Office 35%, Whiteness HP Blue 35%, Whiteness HP Maxx 35%, and Lase Peroxide Sensy 35%. To analyze the degradation of H2O2, the titration of bleaching agents with potassium permanganate was used, while the penetration of H2O2 was measured via spectrophotometric analysis of the acetate buffer solution, collected from the artificial pulp chamber. The analyses were performed immediately as well as 15 minutes, 30 minutes, and 45 minutes after product application. The data of degradation rate of H2O2 were submitted to analysis of variance (ANOVA) and Tukey tests, while ANOVA and Fisher tests were used for the quantification of H2O2, at the 5% level. The results showed that all products significantly reduced the concentration of H2O2 activates at the end of 45 minutes. It was also verified that the penetration of H2O2 was enhanced by increasing the residence time of the product on the tooth surface. It was concluded that the bleaching gels retained substantial concentrations of H2O2 after 45 minutes of application, and penetration of H2O2 in the dental structure is time-dependent.